2022
DOI: 10.3390/ph15030262
|View full text |Cite
|
Sign up to set email alerts
|

A Combined Treatment with Berberine and Andrographis Exhibits Enhanced Anti-Cancer Activity through Suppression of DNA Replication in Colorectal Cancer

Abstract: The high morbidity and mortality associated with colorectal cancer (CRC) are largely due to the invariable development of chemoresistance to classic chemotherapies, as well as intolerance to their significant toxicity. Many pharmaceutical formulations screened from natural plant extracts offer safe, inexpensive, and multi-target therapeutic options. In this study, we demonstrated that Berberis vulgaris L. (Berberine) and Andrographis paniculata (Burm. f.) Nees (Andrographis) extracts exerted their synergistic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 32 publications
(38 reference statements)
1
12
0
Order By: Relevance
“…Colony formation assays were performed as previously reported [ 23 , 40 ]. Five hundred cancer cells were seeded in 6-well plates.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Colony formation assays were performed as previously reported [ 23 , 40 ]. Five hundred cancer cells were seeded in 6-well plates.…”
Section: Methodsmentioning
confidence: 99%
“…For these experiments, 2.5 × 10 5 cells from SW480 and HCT116 lines were treated with each compound for 16 h before total RNA extraction using the MiRNeasy Mini kit (Qiagen, Hilden, Germany). The details for RNA-sequencing library preparation were previously reported [ 12 , 23 , 40 ]. Briefly, the library was constructed using the TruSeq RNA Sample Prep Kit (Illumina, San Diego, CA) with 1 μg of purified RNA input.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell cycle and apoptosis assays were performed using the Muse Cell Analyzer (EMD Millipore Corp, Hayward, CA, USA) according to the manufacturer’s instructions [ 25 , 26 , 33 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 ]. For the cell cycle assays, cells were seeded in 6-well plates and treated with BBR, Gem, and their combination for 48 h. Thereafter, cells were rinsed with ice-cold phosphate-buffered saline (PBS), fixed with 200 μL of ice-cold 70% ethanol and incubated at −20 °C for more than 3 h. Two hundred microliters of Muse TM Cell Cycle Reagent (EMD Millipore Corp) were used in staining cells.…”
Section: Methodsmentioning
confidence: 99%
“…A major constituent of B. vulgaris is berberine which is an isoquinoline alkaloid (a 5,6‐dihydrodibenzo[a,g]quinolizinium) that has various uses in Ayurveda and Traditional Chinese Medicine (McCubrey et al, 2022; Sadeghnia, Kolangikhah, Asadpour, Forouzanfar, & Hosseinzadeh, 2017; Sadeghnia, Taji, Forouzanfar, & Hosseinzadeh, 2017; Xia et al, 2022). Berberine is also present in many other plants including further species of Berberis ( B. aristata L., B. croatica L. , B. aquifolium L.)., Coptis ( Coptis chinensis L., Coptis japonica L.), and Hydrastis ( Hydrastis Canadensis L.) (Imenshahidi & Hosseinzadeh, 2019) and has many pharmacologic properties (Jang, Piao, Kim, Kwon, & Park, 2008), such as antioxidant (Shou et al, 2022), anti‐microbial (Tian et al, 2022), antiinflammatory (Deng et al, 2022), anticancer (Zhao, Roy, Wang, & Goel, 2022), anti‐diabetes (Zhang et al, 2022), anti‐dyslipidemia (Zhao et al, 2021), anti‐obesity (Bhattacharjee, Nath, & Choudhury, 2021), and anti‐metabolic syndrome (Tabeshpour, Imenshahidi, & Hosseinzadeh, 2017). A relatively large number of clinical studies have shown that berberine can display its therapeutic activities in the treatment of different diseases including diabetes, hyperlipidemia, cancer, hypertension, stroke, metabolic syndrome, polycystic ovarian syndrome, and liver disease in human subjects.…”
Section: Introductionmentioning
confidence: 99%